Electrical Circuits Described by General Fractional Conformable Derivative - Kahouli, Omar; Elloumi, Mourad; Naifar, Omar; Alsaif, Haitham; Kahouli, Bassem; Bouteraa, Yassine (Frontiers in Energy Research, 2022)
The general fractional conformable derivative (GCD) and its attributes have been described by researchers in the recent times. Compared with other fractional derivative definitions, this derivative presents a generalization of the conformable derivative and follows the same derivation formulae. For electrical circuits, such as RLC, RC, and LC, we obtain a new class of fractional-order differential equations using this novel derivative, The use of GCD to depict electrical circuits has been shown to be more adaptable and lucrative than the usual conformable derivative.